Water-energy-food nexus of sugarcane ethanol production in the state of Goiás, Brazil: An analysis with regional input-output matrix. (August 2018) - Bellezoni, Rodrigo A.; Sharma, Deepak; Villela, Alberto Arruda; Pereira Junior, Amaro Olimpio
Abstract: Concerns about impacts of biomass growth for biofuel production emphasize the importance of planning energy crops expansion considering land, water, food and biodiversity. Brazil is the second largest ethanol producer worldwide and sugarcane is cultivated in many regions, including the Brazilian Cerrado (a Savannah-type biome). This paper analyses the impacts of first-generation sugarcane expansion in the Paranaíba basin (Goiás State), focusing on how future demand for ethanol could affect local resources availability. The study area is a sugarcane expansion frontier in Brazil, thus, the Cerrado biome should be focus of research considering competition for land and water uses. An economic-ecologic Input-Output (IO) framework was applied to develop a water-energy-food (WEF) nexus analysis. The Goiás' IO table was expanded to assess water, energy and land uses, GHG emissions and employment levels through six different ethanol supply scenarios. Results show that if sugarcane expansion projected to 2030 considers the Goiás' extended IO structure for the year 2008, it should cause little impact on land and water availability in the state, due to both the ample availability of suitable pasturelands for sugarcane expansion as well as water in most of the Paranaíba basin. The WEF nexus analysis is a valuable tool on guiding the sustainable management of natural resources considering water, energy, land use and GHG emissions as goals to the same policy. In particular, the hybrid extended IO-WEF nexus framework is useful to design effective biofuel policies, collectively addressing impacts on environmental, social and economic spheres, in a local or broader context. Highlights: Hybrid IO-WEF nexus framework is useful in analysing integrated biofuel policies. Future 1G ethanol expansion in Goiás has no major impacts on local environment. Sugarcane expansion to areas with water constraints must be restricted. Goiás ethanol expansion might help Brazil to meet its NDCs at the UNFCCC. Biofuel policies should promote replacing 25% of gasoline for ethanol in Goiás.